2010
DOI: 10.3109/08880011003639960
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Oxidative Stress During Chemotherapy of Acute Lymphoblastic Leukemia in Children

Abstract: In this study the authors addressed the question whether neurotoxicity due to the chemotherapy of acute lymphoblastic leukemia (ALL) is associated with cerebrospinal fluid (CSF) oxidative stress. Examination of 38 ALL patients revealed significant increases in 8-isoprostane concentration and important decreases in total antioxidative capacity of CSF during therapy. The mean 8-isoprostane level at diagnosis was 9.05 +/- 1.62 pg/mL, and no correlations with initial leukocytosis, organomegaly, and lactate dehydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 22 publications
3
9
0
Order By: Relevance
“…In summary, the significant increase in oxidized PC and PI reported here, as well as findings from previous studies showing increased F2-isoprostanes 57, 58 provide collective evidence for oxidative stress as a mechanism associated with intrathecal and intravenous chemotherapy. Future studies are needed to investigate novel neuroprotective strategies that could protect healthy brain tissue from oxidative stress while not compromising the anti-leukemic effects of chemotherapeutic agents.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In summary, the significant increase in oxidized PC and PI reported here, as well as findings from previous studies showing increased F2-isoprostanes 57, 58 provide collective evidence for oxidative stress as a mechanism associated with intrathecal and intravenous chemotherapy. Future studies are needed to investigate novel neuroprotective strategies that could protect healthy brain tissue from oxidative stress while not compromising the anti-leukemic effects of chemotherapeutic agents.…”
Section: Discussionsupporting
confidence: 84%
“…This finding supports our hypothesis that CNS treatment disrupts membrane integrity in brain tissue, and increases oxidative stress. Protas and colleagues 58 reported a significant increase in 8-isoprostane concentration (a measure of lipid peroxidation) and decrease in total antioxidant capacity in CSF samples obtained from 38 children with ALL on day 59 of treatment and at 4 time points during intensive CNS-directed treatment which also supports the role of oxidative stress in neurological injury. We reported increased CSF concentrations of F 2 -Isoprostanes during the first 18 months of treatment.…”
Section: Discussionmentioning
confidence: 82%
“…Acute increases in oxidative stress measures were highest among children who received more than six doses of IT MTX during the postinduction phase of treatment. These findings are similar to those of Protas et al (2010) who observed that 8-F 2 -IsoP concentrations were elevated during leukemia treatment.…”
Section: Number Of Doses Of It Mtxsupporting
confidence: 91%
“…However, we were able to find only one study evaluating 8- F 2 -IsoP concentrations in children with cancer. Protas, Muszynska-Roslan, Holownia, Krawczuk-Rybak, and Braszko (2010) found elevated IsoPs in 38 children receiving chemotherapy for leukemia, indicating that neurotoxicity during treatment may be related to oxidative stress.…”
Section: Introductionmentioning
confidence: 97%
“…MTX increases oxidative stress in several organs, including the brain, and white matter is particularly vulnerable to oxidative stress because of its high lipid content (Inder et al, 2002; Rajamani, Muthuvel, Senthilvelan, & Sheeladevi, 2006). Recent studies confirm an association between oxidative stress levels in the cerebrospinal fluid (CSF), MTX, and CNS injury (Caron et al, 2009; Hockenberry et al, 2013; Protas, Muszynska-Roslan, Holownia, Krawczuk-Rybak, & Braszko, 2010; Stenzel et al, 2010). This paper reports clinical presentations of three patients with severe MTX toxicity as well as CSF levels of oxidative stress and apoptosis biomarkers.…”
Section: Introductionmentioning
confidence: 95%